Security Evaluation of MODBUS RTU Protocol, Testing New Cryptographic Methods - Jakabóczki, Gábor; Szemes, Péter Tamás; Ádámkó, Éva (International Journal of Engineering and Management Sciences, 2016)
In the late decade, the number of attacks against SCADA, CIS, or ICS systems had grown considerably. The purpose of this paper is to summarize the results of the implementation of a new cryptographic method on th e MODBUS RTU line.